Comparative Effects of Ingested PVC Micro Particles With and Without Adsorbed Benzo(a)pyrene vs. Spiked Sediments on the Cellular and Sub Cellular Processes of the Benthic Organism Hediste diversicolor - Gomiero, Alessio; Strafella, Pierluigi; Pellini, Giulio; Salvalaggio, Vera; Fabi, Gianna (Frontiers in Marine Science, 2018)
Plastic micro litter represents an emerging contaminant as well as a multiple stress agent in aquatic environments. Microplastics are found even in the remote areas of the world. Together with their occurrence in all environmental compartments, there is a growing concern about their potential to adsorb pollutants co-occurring in the environment. At present, little is known about this source of exposure for aquatic organisms in the benthic environment. Exposure conditions were set up to mimick the contribution of microplastics through different exposure routes. Potential biological effects resulting from these exposures were investigated in the model organism Hediste diversicolor, an annelid worm. Cellular effects including alterations of immunological responses, lysosomal compartment changes, mitochondrial activity, oxyradical production and onset of genotoxicity were assessed in coelomocytes while temporary and permanent effects of oxidative stress were also performed at tissue level. In this study polyvinylchloride (PVC) microparticles were shown to adsorb benzo(a)pyrene with a time and dose-dependent relationship. The elevated bioavailability of the model pollutant after ingestion induced a clear pattern of biological responses. Toxicity mainly targeted impairment of cellular functioning and genotoxicity in H. diversicolor coelomocytes, while permanent effects of oxidative stress were observed at tissue level. Coelomocytes responded fast and with a higher degree of sensitivity to the adverse stimuli. The results showed that microplastic particles in sediments may play a significant role as vectors for organic pollutants. The highest adverse responses were observed in those H. diversicolor exposed to sediments spiked with PVC particles pre-incubated with B[a]P when compared against sediments spiked with B[a]P and plastic microparticles separately.